Results of the Electrolysis Percutaneous Intratissue in the shoulder pain: infraspinatus, A Randomized Controlled Trial - Kazemi, Alireza; R-Moreno, María Dolores (Revista Cubana de Ortopedia y Traumatología, 2016)
Background: The Electrolysis Percutaneous Intratissue (EPI®) is a novel technique that provokes a local inflammatory process, allowing the phagocytises and affected tissue to repair. Objectives: The work is aimed to: a) verify the effectiveness of the EPI® when there is shoulder pain, b) locate where the EPI® should be applied, c) and find the possible interaction between the trigger points and the tendon pain. Design: Randomized controlled trial. Setting: Institute of Physiotherapy and Sports. Method: A double randomized experimental longitudinal study was conducted on four groups of 10 people aged 34-47 years with pain in the shoulder. In the first study there were three intervention groups and a control group. In the second study, the group with the best results in the first study served as a control group. Measurements: The variables measured were the perceived pain and the restriction for abduction, internal and external rotation. Results: Although the three intervention groups improved respect to the control group when the EPI® was applied, the results show that the EPI® is more effective when it is applied in all detected trigger points and to tendon pain. Conclusions: The EPI® is more effective if applied in the infraspinatus muscle and the tendon than applied only to one of the two structures, when both structures have pain. Limitations: The study could have tested the involvement of different structures and its related biomechanical implications. It could have also considered more variables.